2019
DOI: 10.3389/fncel.2019.00290
|View full text |Cite
|
Sign up to set email alerts
|

Role of Corticotropin Releasing Factor in the Neuroimmune Mechanisms of Depression: Examination of Current Pharmaceutical and Herbal Therapies

Abstract: Approximately 3% of the world population suffers from depression, which is one of the most common form of mental disorder. Recent findings suggest that an interaction between the nervous system and immune system might be behind the pathophysiology of various neurological and psychiatric disorders, including depression. Neuropeptides have been shown to play a major role in mediating response to stress and inducing immune activation or suppression. Corticotropin releasing factor (CRF) is a major regulator of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 149 publications
0
30
0
2
Order By: Relevance
“…Results from this present study demonstrated that supplementation with the tropical fruit juice mixture was able to reduce the plasma CRH level in rats following Aβ infusion, suggesting that tropical fruit juice mixture has the potential to prevent the progression of AD by suppressing the activation of HPA axis. Besides that, the increase in the concentration of CRH was positively correlated to depression [68].…”
Section: Discussionmentioning
confidence: 90%
“…Results from this present study demonstrated that supplementation with the tropical fruit juice mixture was able to reduce the plasma CRH level in rats following Aβ infusion, suggesting that tropical fruit juice mixture has the potential to prevent the progression of AD by suppressing the activation of HPA axis. Besides that, the increase in the concentration of CRH was positively correlated to depression [68].…”
Section: Discussionmentioning
confidence: 90%
“…CRF is commonly considered to be a vital factor in response to stress at the neural, endocrinological, and immunological levels [ 9 ]. It is noticeable that CRF is involved in the structural integrity of the brain and in the regulation of neurotransmitter transmission [ 151 ].…”
Section: Chm Modulation Of the Hpa Axismentioning
confidence: 99%
“…In particular, studies have shown that the activation of the neuroinflammatory response of the immune system and hyperactivity of the hypothalamus–pituitary–adrenal (HPA) axis of the neuroendocrine system are two critical triggers in the etiology of depression [ 7 ] ( Figure 1 ). It should be emphasized that communication or crosstalk exists between the neuroimmune and neuroendocrine systems and that the neuroendocrine-immune network plays a vital role in the systems biology of depression [ 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Clear documentation that such interactions exist has largely emerged from recent literature that has benefited from the identification and characterization of pro- and anti-inflammatory cytokines and has analysed their effect upon neural systems. It was clearly established that immune activation alters the turnover of classical neurotransmitters (e.g., noradrenaline, acetylcholine) and activates the HPA axis [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%